Development of a GIS Database for a Water Pipe Distribution System at UTHM Pagoh - Nur Farhanah; Abd Sukor Sarif (Progress in Engineering Application and Technology, 2024)
The development of a Geographic Information System (GIS) database for the water pipe distribution system at Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh addresses key challenges in managing infrastructure. This study focused on creating a Geographic Information System (GIS) database for the water pipes at UTHM Pagoh Campus, managing the water pipe distribution system is challenging due to outdated methods and and inefficiencies, with reliance on paper maps causing operational issues and data handling difficulties. The main goal was to improve how the infrastructure is managed by combining different types of data into one system This upgrade boosts efficiency in maintenance, helps allocate resources more effectively, and enhances decision-making through detailed 3D visualizations and accurate mapping of pipe materials and maintenance records. The objectives are to develop the database and digitize it, as well as to perform the GIS database validation. This GIS database included details like pipe materials, sizes, and maintenance records, making it easier to manage the data, make decisions, and visualize the system. A digital map of the pipe network was created to help with resource allocation and maintenance planning. This new system made managing the water utilities more efficient, improved emergency responses and reduced environmental impacts. By using GIS technology, the project improved the current water pipe management system at UTHM Pagoh, providing a strong tool for maintaining and planning infrastructure.